2014
DOI: 10.1016/j.pain.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic sympathetic block for the treatment of complex regional pain syndrome type I: A double-blind randomized controlled study

Abstract: Pain relief in complex regional pain syndrome (CRPS) remains a major challenge, in part due to the lack of evidence-based treatment trials specific for this condition. We performed a long-term randomized, double-blinded active-control study to evaluate the efficacy of thoracic sympathetic block (TSB) for upper limb type I CRPS. The study objective was to evaluate the analgesic effect of TSB in CRPS. Patients with CRPS type I were treated with standardized pharmacological and physical therapy and were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Sympathetic blocks aim to alleviate the sympathetically mediated pain and can be used in combination with botulinum toxin to prolong the duration of analgesia. Recent evidence has shown sympathetic blockade to provide substantial pain reduction as well as longer analgesic duration, which enable patients to improve participation in functional therapies [9799]. However, there remains a lack of definitive evidence regarding the efficacy of sympathetic blockade overall, and this approach has yet to be shown to be curative [100].…”
Section: Reviewmentioning
confidence: 99%
“…Sympathetic blocks aim to alleviate the sympathetically mediated pain and can be used in combination with botulinum toxin to prolong the duration of analgesia. Recent evidence has shown sympathetic blockade to provide substantial pain reduction as well as longer analgesic duration, which enable patients to improve participation in functional therapies [9799]. However, there remains a lack of definitive evidence regarding the efficacy of sympathetic blockade overall, and this approach has yet to be shown to be curative [100].…”
Section: Reviewmentioning
confidence: 99%
“…[ 5 7 ] One randomized, double-blind active-control study investigated the efficacy of thoracic sympathetic blocks (TSB) for upper limb CRPS type-1. [ 8 ] At 12 months, the average pain scores were significantly lower in the TSB group (3.47 ± 3.5) compared to the control group (5.86 ± 2.9; P = .046). [ 8 ] Also noteworthy is that the scores from the McGill Pain Questionnaire (MPQ), Neuropathic Pain Symptom Inventory (NPSI), and Hospital Anxiety and Depression Scale (HADS) were significantly lower in the TSB group compared to the control group at 1 and at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…From the early 20th century, the sympathetic block has been used in CRPS treatment [ 12 ], and its effects to various extents have been reported with inconsistent level of evidence [ 3 , 13 ]. However, in a recent randomized controlled study, TSGB showed short- and long-term positive effects during the treatment of CRPS in upper extremities [ 14 ].…”
Section: Discussionmentioning
confidence: 99%